Dampak Ekonomi Terhadap Pendapatan Pedagang Kios Di Wisata Religi Makam Sunan Drajat Lamongan - Auliyaur Rohman; Moh. Qudsi Fauzi (Universitas Airlangga, 2016)
This study aims to determine how the economic impact of religious tourism tomb of Sunan Drajat Lamongan on revenues stall traders. The economic impact of tourism generated economic activity of a region in the form of direct economic impact, indirect economic impact, and continued economic impact. The method used is descriptive qualitative approach. Informants in this study are the parties involved in tourism activities, namely tourists, merchants and workers. Technical analysis of the data used is the field analytical techniques and models Miles Hubeman. The direct economic impact of business owners in the form of revenue derived from tourist spending in the tourist locations, namely by 16%. Indirect economic impacts in the form of labor income received by 1.86%, while the continued economic impact is the expenditure of labor which is mostly used for daily needs and consumption.